Nanotubular crystals of garnierite Ni₆ (OH)₈[Si₄O₁₀] - Smolikov, A.; Vezentsev, A.; Beresnev, V.; Pavlenko, V.; Zagorodniuk, L.; Turbin, P. (Вопросы атомной науки и техники, 2015)
The influence of nature of initial components on synthesis conditions and morphology of nanotubular crystals of garnierite (Ni-chrysotile) has been studied. The synthesis of garnierite based on SiO2, Ni(OH)2, and NiSiO3 has been implemented at temperature 673 K and pressure 98.1 MPa in the time interval of 12…15 hours. Nanotubes were formed with an outer diameter of about 20 nm, contained alkali (1…10% NaOH) or salt (0.5…3%). It was shown that the types of tubes “cone in cone” and “tube in tube” are forms appropriate for distilled water. The synthesis conditions and the size of garnierite nanotubes strictly correspond to the parameters, inherent to Mg-chrysotile. Изучено влияние природы исходных компонентов на условия синтеза и морфологию нанотрубчатых кристаллов гарниерита (Ni-хризотила). Осуществлен синтез гарниерита на основе компонентов SiO2, Ni(OH)2 и NiSiO3 при температуре 673 K и давлении 98,1 МПа во временном интервале 12…15 ч. Нанотрубки, сформированные с наружным диаметром ~ 20 нм, содержали щелочь (1…10% NaOH) или соли (0,5…3%). Показано, что типы трубок «конус в конусе» и «трубка в трубке» являются формой соответствующей дистиллированной воде. Условия синтеза и размеры нанотрубок гарниерита строго соответствуют параметрам, характерным для Mg-хризотила. Вивчено вплив природи вихідних компонентів на умови синтезу і морфологію нанотрубчастих кристалів гарнієрита (Ni-хризотилу). Здійснено синтез гарнієриту на основі компонентів SiO2, Ni(OH)2 і NiSiO3 при температурі 673 K і тиску 98,1 МПа в часовому інтервалі 12…15 год. Нанотрубки, сформовані із зовнішнім діаметром ~ 20 нм, містили луг (1…10% NaOH) або солі (0,5…3%). Показано, що типи трубок «конус у конусі» і «трубка в трубці» є формою відповідною дистильованій воді. Умови синтезу і розміри нанотрубок гарнієриту точно відповідають параметрам, характерним для Mg-хризотилу.